2019
DOI: 10.1007/s11605-018-3917-4
|View full text |Cite|
|
Sign up to set email alerts
|

Current Approaches in the Management of Hepatic Adenomas

Abstract: Future genomic-based multicenter studies are required to provide a strong basis for formulating an evidence-based risk-adapted model that guides individualized management strategies for patients with HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 85 publications
0
31
0
Order By: Relevance
“…Based on currently available clinical and molecular risk factors, a personalized treatment algorithm and indications for surgical management of HCA were proposed in a few previous reports [1719]. According to those reports, surgical resection is generally recommended for patients at a substantial risk of complications, such as those with tumor size larger than 5 cm, a tumor increasing in size, presence of the β-catenin-activated subtype, imaging features suggestive of malignancy, concurrent dysplasia and/or the inability to rule out HCC, progressively rising α-fetoprotein levels, and male sex [17, 18]. Therefore, our patient was scheduled to undergo surgical resection due to the largest HCA, larger than 5 cm, and the associated potential risks of rupture and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on currently available clinical and molecular risk factors, a personalized treatment algorithm and indications for surgical management of HCA were proposed in a few previous reports [1719]. According to those reports, surgical resection is generally recommended for patients at a substantial risk of complications, such as those with tumor size larger than 5 cm, a tumor increasing in size, presence of the β-catenin-activated subtype, imaging features suggestive of malignancy, concurrent dysplasia and/or the inability to rule out HCC, progressively rising α-fetoprotein levels, and male sex [17, 18]. Therefore, our patient was scheduled to undergo surgical resection due to the largest HCA, larger than 5 cm, and the associated potential risks of rupture and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Management strategies for HAs depend on the underlying risk factors and size. In patients on hormone replacement therapies (including estrogen and androgen) complete cessation is recommended as studies have shown a regression rate of almost 80% and even complete resolution of the tumor in some patients on stopping OCPs (13). In obese patients, weight loss and even bariatric surgery has proved to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…HAs < 5 cm in size are managed conservatively as they tend to have a benign and uncomplicated clinical course and hence are followed up every 6 months by CT/MRI for the first two years and then annually. In hemodynamically stable patients with bleeding HAs, transarterial embolization (TAE) is considered as the first treatment option, with studies showing a 75% tumor regression rate (13). Limited available data has shown that ablative techniques (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…HCAs are rare monoclonal benign tumors of the liver with an estimated incidence of 3-4/100000 per year in Europe and North America[2,4]. Most HCAs are solitary and usually incidental findings in patients undergoing radiological work up for unrelated or non-specific symptoms[6]. They closely relate to the dose and duration of OCP use, as well as they tend to regress with the withdrawal of hormonal therapy, so its response to hormonal stimulation is questionless according to several studies[1,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, both MRI and biopsy with IHQ are usefull in decision making to help classify HCAs in high or low risk of complications. However, performing a biopsy systematically is still controversial[6]. In the Ronot et al[14] study comparing the efficacy of MRI findings in the diagnosis of these lesions against a routine histological analysis, a 74.5% of agreement between both techniques was observed, with a likelihood ratio of subtype characterization by MRI higher than 20.…”
Section: Discussionmentioning
confidence: 99%